Modificaciones a las funciones del revisor fiscal: Un cambio necesario (2020)
Despite, the importance of guaranteeing the legality and technical quality of financial information, that the tax auditors dictate, these have not been able to update the requirements that have arisen since 2009 with the arrival of Law 1314. For this reason, It is important for the fiscal audit exercise to expose the proposal of the Table 3 of the Superintendency of Companies which seeks to modify Decree 410 of the Commercial Code in force, and analyze whether said proposal adopts the NAI Information Assurance Standards. This is how we managed to conclude, that the proposal made by Table 3 adjusts the functions of the statutory auditor to the requirements of international markets and standards.